Medically Induced Posttraumatic Stress Disorder in Military Personnel and Veterans: An Overview. (2nd October 2019) - O'Garo, Keisha-Gaye N.; Medley, Veronica; Margaretten, Amber R.; Udeaja, Chimezie; Kooistra, Catherine; Eleanya, Akaosa; Koenig, Harold G.
Abstract: Medically induced posttraumatic stress disorder (PTSD) is a growing health concern, given its negative impact on mental, emotional, and physical functioning. There is substantial research that indicates that military personnel and veterans (ADMP/V) are at risk for PTSD. This article explores vulnerability factors that can contribute to the development and exacerbation of PTSD in ADMP/V in medical or surgical settings. The results indicate that ADMP/V are at least as vulnerable as their civilian counterparts in developing medically induced PTSD. Interventions that enhance protective factors and promote resiliency in this population are essential for effectively managing traumatic response to medical treatments.